Fat, sugar and water intakes among families from the IDEFICS intervention and control groups: first observations from I.Family. (December 2015) - Arvidsson, L.; Bogl, L.‐H.; Eiben, G.; Hebestreit, A.; Nagy, P.; Tornaritis, M.; Moreno, L. A.; Siani, A.; Veidebaum, T.; De Henauw, S.; Lissner, L.; ,
Summary: Background: The objective of this paper is to investigate differences in diets of families in intervention versus control communities 5 years after the Identification and Prevention of Dietary‐ and Lifestyle‐Induced Health Effects in Children and Infants intervention ended. Methods: Altogether, 4, 691 families from the I.Family study with at least one participating parent and one child are included in this analysis. Diet quality indicators, defined as propensities to consume fat, sugar, water and fruit and vegetables, are calculated from a 59‐item food frequency questionnaire. Multilevel linear models with random intercepts for study centre are used to determine whether mean diet indicators, calculated at the family level, differed as a function of previous exposure to the intervention. Results: Families in the intervention communities reported a significantly lower sugar propensity (19.8% vs. 20.7% of total food items, p < 0.01) and a higher water propensity (47.3% vs. 46.0% of total beverages, p < 0.05) compared with families in the control communities, while fat and fruit and vegetables propensities were similar. No significant diet differences between intervention and control children were present at the Identification and Prevention of Dietary‐ and Lifestyle‐Induced Health Effects in Children and Infants baseline. Discussion: This result indicates better diet quality in intervention families, which was not present in children when their diets were assessed before the intervention, and gives some cause for optimism regarding the sustainability of some aspects of the diet intervention.